Fight / Sloane St. James. - St. James, Sloane (Sky Ridge hotshots., 2025)
Fighting wildfires is the only thing I've ever wanted to do and I'm damn good at it. Being the captain of an interagency hotshot crew of wildland firefighters is high-risk, high reward. But the risk blindsided me five years ago when I lost one of my crew and it changed me forever. Now I work harder, smarter, and the only rewards I allow myself to enjoy easy, sexy nights with strangers. Until I meet Prescott Timmons. Her smart-mouth and adventurous spirit have me forgetting all my rules - except when her past shows up, my lies start to feel too familiar. I swear to never spare her a second glance, but when she finds herself in a life-or-death situation with mother nature, my instincts kick in, and I take action. Stranded and sharing a bed again, we're forced to face our truth.